INCLUSIVE EDUCATION AND TEACHER TRAINING IN EARLY CHILDHOOD EDUCATION - de Jesus Dias da Silva, Terezinha (Revista Gênero e Interdisciplinaridade, 2023)
The general objective of this study is to analyze the importance of teacher training to improve inclusive education in early childhood education. Inclusive education presents significant challenges for early years teachers, as demonstrated by an exploratory qualitative study that incorporated bibliographic and documentary research methods. Given the data presented, it is essential to reflect on the need to adapt regular education to the inclusion scenario, given the long path taken by those who go through in the name of operationalizing this process. In this way, the research data showed that there is still a very marked discrepancy in the issue of teaching with this public, since there is still a lack of incentives, mainly for professionals working in this context, thus affecting the quality of the teaching offered, and in addition, making the long-awaited inclusion difficult. In this way, the research data showed that there is still a very marked discrepancy in the issue of teaching with this public, since there is still a lack of incentives, mainly for professionals working in this context, thus affecting the quality of the teaching offered, and in addition , making the long-awaited inclusion difficult.